ANALYZING THE EFFECT OF JOB SATISFACTION AND EMPLOYEE WORK EXPERIENCE ON EMPLOYEE PERFORMANCE LOYALTY: (Case Study: Assalam Hypermarket) - avika, isma ridha; paradhita, astrid noviana (Jurnal Manajemen Bisnis dan Terapan, 2000)
Human resources or HR is one of the elements in the company that is quite important to ensure the smooth running of operational activities in the company. Employee satisfaction and work experience are several factors in maintaining the level of employee performance loyalty in a company. This study was conducted to examine the relationship between the influence of job satisfaction and work experience felt by employees on the level of employee performance loyalty at Assalaam Hypermarket. This study collects data with questionnaires from 100 sample data of employees who work at Assalam Hypermarket. The discussion method used is descriptive quantitative by testing several instrument items that describe the level of satisfaction and work experience of employees using validity and reliability tests. After that, the researcher analyzes using multiple linear regression techniques. In this study, researchers used the SPSS application to conduct tests. From this study, it was concluded that job satisfaction had an effect of 64.5% and work experience had an effect of 28.5% on the level of employee performance loyalty in the company. The results showed that several aspects of work experience still need to be improved by Assalam Hypermarket.